The Welfare Level of Farmers in The Implementation of Integration System of Farming Rice and Beef Cattle in Small Household Scale in Buke Sub-District, South Konawe District - Fyka, Samsul Alam; Abdullah, Bahari; Limi, Muhammad Aswar; Salamah, Salamah; Fitriaman, Fitriaman (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
Integration system is an effort to improve the welfare level of farmers. The objective of this study was to determine the welfare level of farmers as the implementers of integration system of rice and beef cattle. The research method was quantitative descriptive with samples of 25 farmers who applied integration system selected purposively. The data analysis used was the analysis of income and welfare level by using the approach of Southeast Sulawesi Provincial Minimum Wage (UMP) in 2019 and the poverty line of the farmers’ families. The results of the study were that the farmers who applied integration system of farming rice and beef cattle had different welfare level, in which 40% of farmers were classified as prosperous because their income from the integration system is greater than the UMP. Meanwhile, the remaining 60% farmers were classified as not prosperous because their income is smaller than the Southeast Sulawesi UMP and the average farmer was above the poverty line in the district of South Konawe